Time‐series analysis of long‐term photometry of BM Canum Venaticorum1. Issue 4 (16th February 2017) - Siltala, L.; Jetsu, L.; Hackman, T.; Henry, G. W.; Immonen, L.; Kajatkari, P.; Lankinen, J.; Lehtinen, J.; Monira, S.; Nikbakhsh, S.; Viitanen, A.; Viuho, J.; et al.
Abstract : Long‐term photometry is commonly used to monitor chromospheric activity of late–type stars. We study standard Johnson differential V photometry of the RS CVn binary BM Canum Venaticorum (BM CVn) spanning over a quarter of a century. Our main aims are to determine the activity cycles, the rate of surface differential rotation, and the rotation period of the active longitudes of BM CVn. The continuous period search (CPS) algorithm is applied to the photometry. The changes of the mean and amplitude of the light curves are used to search for activity cycles. The rotation period changes give an estimate of the rate of surface differential rotation. The Kuiper method is applied to the epochs of the primary and secondary minima to search for active longitudes. The photometry reveals the presence of a stable mean light curve (MLC) connected to the orbital period P orb =20. d 6252 of this binary. We remove this MLC from the original V magnitudes, which gives us the corrected V ′ magnitudes. These two samples of V and V ′ data are analyzed separately with CPS. The fraction of unreliable CPS models decreases when the MLC is removed. The same significant activity cycle of approximately 12.5 years is detected in both V and V ′ samples. The estimate for the surface differential rotation coefficient, k ⩾0.10, is the same for both samples, but the number of unrealistic period estimates decreases after removing the MLC. The same active longitude period of P al =20. d 511 ± 0. d 005 is detected in the V and V ′ magnitudes. This long‐term regularity in the epochs of primary and secondary minima of the light curves is not caused by the MLC. On the contrary, the MLC hampers the detection of active longitudes.